Identification of Species Composition of Harmful Entomofauna in Seed Storehouses of Some Field Crops - Ter-Grigoryan, A. J.; Manvelyan, A. A.; Ghazaryan, M. H. (ՀԱԱՀ հիմնադրամ)
In 2018-2019, 8 species of pests were registered in the warehouses of seeds of different crops, which were located in the cities of Yerevan, Abovyan and Masis, (Sitophilus granaries L., Trogoderma granarium Ev., Tenebrioides mauritanicus L., Sitophilus oryzae L., Rhyzopertha dominica F., Acanthoscelides obtectus Say., Callosobruchus maculatus Fabr., Sitophilus oryzae L., Bruchophagus roddi Guss). In all three warehouses, wheat and barley were the most infected with pests, while sainfoin was not damaged in any of the warehouses.
Keywords: Agronomy and Agroecology